2006
DOI: 10.1038/sj.onc.1210141
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal instability by β-catenin/TCF transcription in APC or β-catenin mutant cells

Abstract: Adenomatous polyposis coli (APC/Apc) gene encodes a key tumor suppressor whose mutations activate b-catenin/ T-cell factor (TCF)-mediated transcription (canonical Wnt signaling). Here, we show that Wnt signaling can cause chromosomal instability (CIN). As an indicator of CIN, we scored anaphase bridge index (ABI) in mouse polyps and ES cells where Wnt signaling was activated by Apc or b-catenin mutations. We found three to nine times higher ABI than in wild-type controls. Furthermore, karyotype analysis confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 41 publications
4
54
0
3
Order By: Relevance
“…We have recently found significantly high anaphase bridge index (ABI), a marker of CIN, in the intestinal polyp epithelium and ES cells mutated in Apc or b-catenin gene. Importantly, such high ABI were reversed when the cells were introduced with dominant-negative TCF constructs, indicating that transcriptional activation was responsible (Aoki et al, 2006). Consistent with our observation, it has been shown that Wnt signaling causes CIN via upregulation of conductin (axin2) (Hadjihannas et al, 2006).…”
Section: Modifier Genes Of Apc Intestinal Polyposissupporting
confidence: 88%
“…We have recently found significantly high anaphase bridge index (ABI), a marker of CIN, in the intestinal polyp epithelium and ES cells mutated in Apc or b-catenin gene. Importantly, such high ABI were reversed when the cells were introduced with dominant-negative TCF constructs, indicating that transcriptional activation was responsible (Aoki et al, 2006). Consistent with our observation, it has been shown that Wnt signaling causes CIN via upregulation of conductin (axin2) (Hadjihannas et al, 2006).…”
Section: Modifier Genes Of Apc Intestinal Polyposissupporting
confidence: 88%
“…Activated Wnt signaling resulting from stabilized ␤-catenin was recently reported to contribute to chromosome instability (Aoki et al, 2007) and lead to G2 arrest (Olmeda et al, 2003). Thus, we predicted that the abnormal nuclear morphology seen in cells expressing M2-APC was dependent on M2-APC association with and stabilization of nuclear ␤-catenin.…”
Section: The Abnormal Nuclear Morphology After Expression Of the 15-amentioning
confidence: 82%
“…In addition, it has been shown in vivo that mechanical irritation of the epithelium can lead to an increased mutation rate (Takahashi et al, 2000). This suggests that cells of the APC deficient colon, which can already experience chromosomal missegregation due to dominant negative effects of truncated APC protein or insufficient full length APC during mitosis (Fodde et al, 2001;Tighe et al, 2004;Aoki et al, 2007;Draviam et al, 2006), may be exposed to an alternative route to loss of heterozygosity when subjected to mechanical stress, in addition to the effects demonstrated here on tumor gene expression in the haploinsufficient tissue.…”
Section: Discussionmentioning
confidence: 99%